Immunogenicity, safety, and tolerability of a recombinant measles-virus-based chikungunya vaccine: a randomised, double-blind, placebo-controlled, active-comparator, first-in-man trial. Issue 5 (May 2015) - Ramsauer, Katrin; Schwameis, Michael; Firbas, Christa; Müllner, Matthias; Putnak, Robert J; Thomas, Stephen J; Desprès, Philippe; Tauber, Erich; Jilma, Bernd; Tangy, Frederic
Summary Background Chikungunya is an emerging arthropod-borne disease that has spread from tropical endemic areas to more temperate climates of the USA and Europe. However, no specific treatment or preventive measure is yet available. We aimed to investigate the immunogenicity and safety of a live recombinant measles-virus-based chikungunya vaccine. Methods We did a randomised, double-blind, placebo-controlled, active-comparator, phase 1, dose-escalation study at one centre in Vienna, Austria. Healthy men and women aged 18–45 years with no comorbidities were randomly assigned, by computer-generated block randomisation (block size of 14), to receive either one of three escalating doses of the measles-virus-based candidate vaccine (low dose [1·5 × 104 median tissue culture infection doses (TCID50) per 0·05 mL], medium dose [7·5 × 104 TCID50 per 0·25 mL], or high dose [3·0 × 105 TCID50 per 1·0 mL]), or the active comparator—Priorix. Participants were additionally block-randomised to receive a booster injection on either day 28 or day 90 after the first vaccination. Participants and study investigators were masked to group allocation. The primary endpoint was the presence of neutralising anti-chikungunya antibodies on day 28, as assessed by 50% plaque reduction neutralisation test. Analysis was by intention to treat and per protocol. This trial is registered with EudraCT, number 2013-001084-23. Findings Between Nov 22, 2013, and Feb 25, 2014, we randomly assigned 42 participants to receive the low dose (n=12), the medium dose (n=12), or the high dose (n=12) of the measles-virus-based candidate vaccine, or Priorix (n=6), of whom 36 participants (86%; n=9, n=12, n=10, n=5, respectively) were included in the per-protocol population. The candidate vaccine raised neutralising antibodies in all dose cohorts after one immunisation, with seroconversion rates of 44% (n=4) in the low-dose group, 92% (n=11) in the medium-dose group, and 90% (n=10) in the high-dose group. The immunogenicity of the candidate vaccine was not affected by pre-existing anti-measles immunity. The second vaccination resulted in a 100% seroconversion for all participants in the candidate vaccine groups. The candidate vaccine had an overall good safety profile, and the rate of adverse events increased with vaccine dose and volume. No vaccination-related serious adverse events were recorded. Interpretation The live recombinant measles-virus-based chikungunya vaccine had good immunogenicity, even in the presence of anti-vector immunity, was safe, and had a generally acceptable tolerability profile. This vaccine is the first promising measles-virus-based candidate vaccine for use in human beings. Funding Themis Bioscience GmBH.